SOLUTION: simplify using cramer's rule:- x-y=1 x+z=-6 x+y-2z=3
-> SOLUTION: simplify using cramer's rule:- x-y=1 x+z=-6 x+y-2z=3
: algebra software solves algebra homework problems with step-by-step help!
solves your algebra problems and provides step-by-step explanations!
Algebra: Matrices, determinant, Cramer rule
If you need
immediate math help from PAID TUTORS right now
, click here
. (paid link)
Click here to see ALL problems on Matrices-and-determiminant
simplify using cramer's rule:-
put this solution on YOUR website!
z=2, if your problem is x+z=6
however, if your problem is x+z=-6,your answer is z=-4